2005
DOI: 10.1302/0301-620x.87b5.15794
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for arthroscopic treatment of anterior instability of the shoulder

Abstract: We prospectively evaluated 61 patients treated arthroscopically for anterior instability of the shoulder at a mean follow-up of 44.5 months (24 to 100) using the Rowe scale. Those with post-operative dislocation or subluxation were considered to be failures. Logistic regression analysis was used to identify patients at increased risk of recurrence in order to develop a suitable selection system. The mean Rowe score improved from 45 pre-operatively to 86 at follow-up (p < 0.001). At least one episode of post-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 38 publications
3
64
1
9
Order By: Relevance
“…In addition, eight patients (13%) had persistent apprehension or pain with an anterior apprehension test. Several poor prognostic factors for recurrent instability after an open Bankart repair have been described [8,10,12,22,26,37,39,58]. In our series, patients younger than 25 years showed a trend for a higher risk of recurrence.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, eight patients (13%) had persistent apprehension or pain with an anterior apprehension test. Several poor prognostic factors for recurrent instability after an open Bankart repair have been described [8,10,12,22,26,37,39,58]. In our series, patients younger than 25 years showed a trend for a higher risk of recurrence.…”
Section: Discussionsupporting
confidence: 51%
“…The rationale for this indication is to reconstruct the glenoid surface with the coracoid. There is not clear consensus on the minimum size of the bony lesion to indicate the procedure, but we found that glenoid loss of more than 15 % of the inferior glenoid diameter represents a superior risk of postoperative recurrence after shoulder stabilization with arthroscopic Bankart [8].…”
Section: Indications For Coracoid Transfer Techniquesmentioning
confidence: 71%
“…Boileau et al (4) , em seu trabalho de 2006, observaram que os fatores que predispõem à recidiva pós-operatória são perda óssea substancial, seja no úmero ou na cavidade glenoidal, e distensão capsular provocada por repetidos episó-dios de luxação (Figuras 4 e 5). Outros autores também têm demonstrado que a erosão na borda anteroinferior da cavidade glenoidal é um fator importante no aumento da taxa de recidiva dos pacientes operados por luxação recidivante traumática anterior do ombro (4,(13)(14)(15)(16) . Em nosso estudo, os pacientes apresentavam em mé-dia 18 episódios de luxação no momento da cirurgia, que julgamos ser um número elevado e injustificável de episódios para uma afecção que tem sua indicação cirúrgica classicamente orientada após o seu segundo episódio.…”
Section: Resultsunclassified